2009
DOI: 10.1038/labinvest.2008.110
|View full text |Cite
|
Sign up to set email alerts
|

Reduced acetaminophen-induced liver injury in mice by genetic disruption of IL-1 receptor antagonist

Abstract: Acetaminophen (APAP) induced increases in intrahepatic expression of interleukin (IL)-1a, IL-1b, and IL-1 receptor antagonist (IL-1ra), when administered intraperitoneally. These observations prompted us to define the pathophysiological roles of IL-1ra in APAP-induced liver injury. Compared with wild-type (WT) mouse-derived hepatocytes, IL-1ra-deficient (IL-1ra KO)-derived hepatocytes exhibited more resistance against APAP but not APAP-derived major toxic metabolite, N-acetyl-p-benzoquinone imine (NAPQI). More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 56 publications
(88 reference statements)
1
30
1
1
Order By: Relevance
“…IL-1β was an important effector cytokine in innate immune and inflammation (18). Blocking IL-1β signaling also alleviated liver injury (12,32). In present study, IL-1β expression was upregulated in the liver tissues and blood by chloroform administration.…”
Section: Discussionsupporting
confidence: 49%
“…IL-1β was an important effector cytokine in innate immune and inflammation (18). Blocking IL-1β signaling also alleviated liver injury (12,32). In present study, IL-1β expression was upregulated in the liver tissues and blood by chloroform administration.…”
Section: Discussionsupporting
confidence: 49%
“…Furthermore, the amounts of a major APAP adduct (seleniumbinding protein), an indicator of NAPQI generation from APAP, were also found to be significantly lower in IL-1ra KO mice than in WT mice along with depressed intrahepatic expression of cytochrome P450 enzymes (such as CYP1A2, CYP2E1 and CYP3A11), the enzymes crucially involved in NAPQI generation from APAP. 12 These observations showed that IL-1ra deficiency impaired APAP metabolism and suggested that rhIL-1Ra would not attenuate the hepatotoxicity of APAP. On the contrary, it may even exacerbate hepatotoxicity.…”
Section: Discussionmentioning
confidence: 95%
“…11 At present, it is known that expressions of IL-1 and IL-1Ra in tissue are enhanced significantly and that the intrahepatic IL-1 level is correlated with the severity of organ damage in APAP-induced liver injury. [12][13][14][15] Blazka et al showed that the administration of anti-IL-1 antibody attenuated APAP-induced liver injury and that the administration of anti-IL-1Ra antibody exacerbated organ injury. However, IL-1Ra (4 ml/kg) that was administered 30 min before APAP had only a modest protective effect against APAP-induced liver injury on decreasing serum enzyme release, and had no effect on the degree of hepatic congestion or necrosis.…”
mentioning
confidence: 99%
“…Thus, the production of proinflammatory cytokines such as IL-1, TNF-␣, and IL-6 may be linked. Moreover, Ishibe et al found that nuclear NF-B p65 protein levels were higher in untreated hepatocytes from IL-1Ra KO mice (BALB/c background) than in those from WT mice, although cytosolic NF-B p65 protein levels did not differ (62). Hence, an IL-1Ra gene deficiency increases the expression of IL-1 and other inflammatory cytokines through NF-B activation, and upregulated inflammatory cytokines enhance RANKL and M-CSF mRNA expression in our experiment as well.…”
Section: Discussionmentioning
confidence: 99%